2022
DOI: 10.3389/fmicb.2022.916061
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Signatures in the Progression of Hepatitis B Virus-Induced Liver Disease

Abstract: The gut microbiome is associated with hepatitis B virus (HBV)-induced liver disease, which progresses from chronic hepatitis B, to liver cirrhosis, and eventually to hepatocellular carcinoma. Studies have analyzed the gut microbiome at each stage of HBV-induced liver diseases, but a consensus has not been reached on the microbial signatures across these stages. Here, we conducted by a systematic meta-analysis of 486 fecal samples from publicly available 16S rRNA gene datasets across all disease stages, and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Note that all the records concerning HAV and HDV were excluded ( Figure 1 ). Among the 12 included studies from PubMed, 1 was about HEV infection( Wu et al., 2020 ), 4 were about HCV infection( Aly et al., 2016 ; Taylor et al., 2020 ; Sultan et al., 2021 ; Ali et al., 2023 ), and 7 were HBV-related liver disorders ( Wang et al., 2017 ; Liu et al., 2018 ; Liu et al., 2019 ; Ni et al., 2019 ; Chen et al., 2020 ; Zheng et al., 2020 ; Li et al., 2022 ). The remaining unpublished data was from BioProject and concerned HBV (BioProject accession number PRJEB32568).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that all the records concerning HAV and HDV were excluded ( Figure 1 ). Among the 12 included studies from PubMed, 1 was about HEV infection( Wu et al., 2020 ), 4 were about HCV infection( Aly et al., 2016 ; Taylor et al., 2020 ; Sultan et al., 2021 ; Ali et al., 2023 ), and 7 were HBV-related liver disorders ( Wang et al., 2017 ; Liu et al., 2018 ; Liu et al., 2019 ; Ni et al., 2019 ; Chen et al., 2020 ; Zheng et al., 2020 ; Li et al., 2022 ). The remaining unpublished data was from BioProject and concerned HBV (BioProject accession number PRJEB32568).…”
Section: Resultsmentioning
confidence: 99%
“…The PCoA and NMDS analyses were conducted with PERMANOVA and ANOSIM, respectively, to evaluate the similarities in the gut microbiome composition among the groups in all the included studies. The PERMANOVA and ANOSIM results for the datasets of PRJEB32568 and PRJNA838083 ( Li et al., 2022 ) reporting four separate groups (HC, CHB, HBV-LC, and HBV-HCC) indicated that as HBV infection progressed, there were significant differences in species composition between the groups ( P < 0.01; Figures 7 , 8 ). The PERMANOVA results for the PRJNA558158 ( Chen et al., 2020 ) and PRJNA540574 ( Zheng et al., 2020 ) datasets showed the same trend ( P < 0.01; Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-chain fatty acids, especially butyrate, produced by gut microbiota were reported to suppress inflammatory response and oxidative stress ( Hu et al, 2013 ). Besides, Monoglobus was enriched in health individuals, and its abundance was positively correlated with CD4+ T cell counts ( Li R. et al, 2022 ; Wang et al, 2022 ). CD4(+) T cells play crucial roles in adaptive immune response against pathogens ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the causative relation between the microbiome and HBV replication is very complicated, and has not yet been adequately clarified. Briefly, some studies have shown that HBV infection alters the microbiome [ 34 , 35 ], whereas others have shown that, conversely, the gut microbiome can affect HBV replication and disease progression. In mice, fecal transplant can significantly alter HBV replication and disease progression [ 36 ].…”
Section: Interactions Between Hbv Infection Metabolism and Hormonesmentioning
confidence: 99%